Effects of a Video-Based Preoperative Educational Intervention Plus Nurse-Led Reinforcement Discussion on Knowledge, Self-Efficacy, and Resilience in Patients Undergoing Major Surgery. (July 2021) - Gonella, Silvia; Delfino, Cristina; Rolfo, Monica; Rizzo, Alessio; Esposito, Valeria; Berchialla, Paola; Campagna, Sara
This study aimed to verify the feasibility of a video-based preoperative educational intervention plus one-to-one, nurse-led reinforcement discussion in patients undergoing elective major surgery and to assess the impact of this combined intervention on patient- and nurse-perceived patient knowledge, self-efficacy, and resilience. Patients received written material at pre-admission and were offered the intervention at admission. Patients reported their knowledge and self-efficacy at pre-admission and after the intervention, and resilience at pre-admission and discharge. Nurses assessed patients' knowledge and self-efficacy after the intervention. In all, 88/97 (90.7%) patients completed the intervention. The 80 patients with complete data reported a significant increase in their knowledge ( p  < .001) and self-efficacy ( p  < .001), but no difference in resilience ( p  = .72). Nurse-perceived patient knowledge agreed with patients' perceptions ( p  = .57) but nurses scored patients' self-efficacy lower ( p  < .001). The combined intervention was feasible, and patients perceived an improvement in their knowledge and self-efficacy. Nurses' assessment partially agreed with patients' perceptions.